DESIGN AND CONSTRUCTION OF WATER FILTER MODEL WITH ZEFAR MEDIA AND BACKWASH METHOD FOR MEDIA CLEANING - Martoni; Farida, Ida; Santoso, Heru (CENTRAL ASIA AND THE CAUCASUS, 2022)
From the results of research that has been done previously, which is entitled "RESEARCH OF THE INFLUENCE OF FILTER MEDIA COMPOSITION ON THEQUALITY OF FILTERED WATER" followed by the design of a water filter device model by utilizing ZEFAR filter media (Zeolite, Ferrolite and Activated Charcoal) with a frame using elbow steel with joints bolts and equipped with a backwash system, which is a system that aims to extend the service life of the media and make it easier to clean the media without having to remove it from the main tube. The design of this filter model aims to make it easier to test the quality of water filters with different compositions and types and ratios of filter media so that the best filtering days can be obtained.